Synthesis and characterization of new 3,3`-bipyrazole-4,4`-dicarboxylic acid derivatives and some of their palladium(II) complexes as pre-catalyst for Suzuki coupling reaction in water - Al-Fulaij, Othman Abduallah; Elassar, Abdel-Zaher Abdelaziz; Dawood, Kamal Mohamed (European Journal of Chemistry, 2019)
The 1,3-dipolar cycloaddition reaction of bis-hydrazonyl chlorides with methyl propiolate afforded dimethyl 1,1¢-aryl-3,3`-bipyrazole-4,4`-dicarboxylates (5a,b). Heating the later compound 5a with a mixture of HCl/AcOH gave 3,3`-bipyrazole-5,5`-dicarboxylic acid derivative 6. Treatment of the hydrazonoyl chloride (1a) and 3,3`-bipyrazole-5,5`-dicarboxylic acid (6) with palladium(II) chloride gave the corresponding Pd-complexes 7 and 8, respectively. The catalytic activity of the prepared Pd-complexes was examined in the Suzuki cross-coupling reaction of phenylboronic acid with activated and deactivated aryl(hetaryl) bromides. The catalyst system provides very good to excellent yields, 85-94%. The structures of the obtained products were established from their elemental analysis, spectral data, XPS, EDX, and single crystal X-ray crystallography. Crystal data for C10H7N2O2 (6): triclinic, space group P-1 (no. 2), a = 3.9956(10) Å, b = 9.8917(18) Å, c = 10.810(3) Å, α = 94.167(15)°, β = 94.979(19)°, γ = 98.953(15)°, V = 418.83(16) Å3, Z = 2, T = 296.(2) K, μ(Cu Kα) = 0.887 mm-1, Dcalc = 1.484 g/cm3, 5469 reflections measured (11.72° ≤ 2Θ ≤ 133.24°), 1420 unique (Rint = 0.0633, Rsigma = 7.24%) which were used in all calculations. The final R1 was 0.1055 (>2sigma(I)) and wR2 was 0.3620 (all data).